Effects of Home Tutoring Programme on Reading Comprehension Scores of Primary School Pupils with Dyslexia in Suleja, Niger State, Nigeria - Liman, Nalado A. (NIU Journal of Humanities; Vol 6 No 1 (2021): KIU Journal of Humanities, Vol. 6 No. 1, March 2021, 2021)
This study examined the effects of home tutoring programme on reading comprehension scores of primary school children with dyslexia in Suleja Local Government Area of Niger state, Nigeria. The study adopted quasi experimental design, and particularly it employed the pretest - posttest control – experimental group design. A sample of eight (8) pupils was taken (four in the experimental and four in the control group). Two research questions and three hypotheses guided the study. The instrument for data collection was the Umolu Informal Reading Inventory (UIRI), which was validated and found to be appropriate for the study. A data analysis was done using simple percentage, mean difference and gain scores to answer research questions and t-Test to answer the hypotheses. The results obtained revealed that children taught using home tutoring programme performed better in reading comprehension than children taught with the conventional method, it was recommend that parents should procure the services of a home tutor for their children with dyslexia so as to improve their reading comprehension. Keywords : Home Tutoring, Reading Comprehension and Pupils with dyslexia